Tokenomics and Digital Economy in China: Analyzing the Influence of Blockchain Technology Integration on Traditional Business Models - Fadi Ghosn; Mohamad Zreik; Hala Koleilat Al Dilby; Caroline Dib Kassably Fakhry; Fida Ragheb Hassanein (Economies)
This study investigates the impact of tokenomics and the integration of blockchain technology on China’s digital economy, focusing on how blockchain adoption influences traditional business models. As China becomes a global leader in digital transformation, understanding the role of the blockchain in economic modernization is critical. The aim of this research is to quantify the effects of blockchain adoption on key economic indicators such as GDP growth, investment levels, and business innovation. Using panel data analysis and regression models, this study provides empirical evidence on the positive correlation between blockchain integration and improved economic performance. Key results reveal that a 1% increase in blockchain adoption is associated with a 0.3% rise in GDP growth, while tokenization contributes significantly to investment levels and business innovation. These findings emphasize the transformative potential of the blockchain in enhancing economic stability, increasing liquidity, and fostering new business opportunities. In conclusion, this research highlights the critical role of the blockchain and tokenomics in driving economic modernization in China, offering valuable insights for policymakers, business leaders, and investors aiming to leverage digital technologies for sustainable growth. Future research should explore the broader global implications of blockchain adoption and tokenomics in emerging markets.